Bibliometric Analysis: Artificial Intelligence (AI) in High School Education - Triansyah, Fadli Agus; Muhammad, Ilham; Rabuandika, Andi; Siregar, Kartika Dwi Pratiwi; Teapon, Nurhuda; Assabana, Mohammad Syahru (Universitas Pendidikan Ganesha, 2023)
One of the technologies that can be used in education is Artificial Intelligence (AI). Artificial intelligence (AI) is the ability of machines or computer programs to imitate or perform tasks that normally require human intelligence, such as decision-making, speech or image recognition, and problem-solving. The purpose of this research is to analyze publications related to Artificial Intelligence (AI) in Middle Schools and to describe the characteristics of this research. The method used is descriptive bibliometric analysis. The Scopus database is used to obtain the necessary data. The research results show that publications have increased from 9 in 2021 to 20 in 2020. Publications in 2010 have been cited more than any other year. China is the most influential country in this field. Most publications on Artificial Intelligence research applied to high school students are at the Q1 rank, namely 25 journals. New themes in this field are machine learning and deep learning. Artificial Intelligence has not been directly connected with some third clusters keywords such as Artificial Intelligence Literacy, computer science education, and conception.